Social Media and Democracy The State of the Field, Prospects for Reform - Persily, Nathaniel; Tucker, Joshua A. (Social Sciences, 2020)
This book is a state-of-the-art account of what we know and do not know about the impact of digital technology on democracy. It will interest scholars, policymakers, and philanthropic organizations. This title is also available as Open Access on Cambridge Core.